PROBLEMS RELATED TO THE PRACTICE OF USING INDICATORS TO ASSESS THE EFFECTIVENESS OF COMMERCIAL BANKS’ ASSETS IN OUR COUNTRY - Kholmuradov, Musurmon Avlakulovich; Karimboeva, Sarvinoz Bakhtiyorovna (THE INNOVATION ECONOMY, 2026)
Ensuring the quality of asset portfolios of commercial banks, the need to ensure their financial stability and liquidity is considered one of the current issues. In this scientific article, an attempt was made to develop a scientific proposal and practical recommendations on ways to increase the efficiency of the assets of commercial banks.